Notes on the diatom collection of the Natural History Museum, London (BM) X: Roper’s species of Biddulphia (Bacillariophyta) - Williams, David M.; Sims, Pat A.; Ashworth, Matt P. (Phytotaxa, 2026)
Freeman Clarke Samuel Roper described three new taxa of Biddulphia: B. granulata, B. reticulata and the invalidly published B. reticulata var. β. His original drawings of these have been discovered as in most cases they identify the exact slide (and sometime the exact specimen) used for his study. These have been examined here and, in some cases, revised names of certain species studied by us earlier are proposed.